Familiarity with crypto and financial concepts: Cryptoasset owners, non-owners, and gender differences - Daniela Balutel; Walter Engert; Christopher Henry; Kim P. Huynh; Doina Rusu; Marcel-Christian Voia (Bank of Canada, 2024)
In the rapidly evolving landscape of digital asset markets, measuring cryptoasset knowledge alongside financial knowledge enhances our understanding of individuals' decisions to purchase cryptoassets. Using microdata from the Bank of Canada's Bitcoin Omnibus Survey, we measure familiarity with crypto concepts using a set of three questions covering basic aspects of Bitcoin. Familiarity with financial concepts is measured using a set of three questions covering basic aspects of conventional finance. We also consider gender differences across these measures. A novel aspect of this paper is an empirical joint analysis that allows us to consider the interrelationship between these two measures of crypto and financial knowledge.
Keywords: C81; D14; D91; G53; O51; 330; Central bank research; Digital currencies and fintech; Econometric and statistical methods